The Analysis of Repetition in the Body Text of Shampoo Advertisements - Nurjannah, Nunung (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2015)
This research is intended to analyze the repetition in the body text of shampoo advertisements. The objectives of this research are: first, to describe what types of repetitions are used in the body text of shampoo advertisements. Second, to find out which repetition is most often used in the body text of shampoo advertisements. Third, to find out why certain repetition is most often used in the body text of shampoo advertisements. This is a qualitative research. Therefore, it uses descriptive method with the theories of repetition proposed by Halliday and Hasan (1976), Renkema (1993), Hoey (1991) and Halliday (1994), the theories of discourse proposed by Halliday (1985), Renkema (1993) and Nunan (1993), and the theories of advertisement proposed by Cook (1992) and Moi (1997). At the end of the analyses the writer found that the repetitions in the body text of shampoo advertisements are classified into simple repetition and complex repetition. Simple repetition is the most dominant types of repetition that used in the body text of shampoo advertisements because the use of simple repetition in the body text of shampoo advertisements is very important to make the readers or consumers understand and remember the name of the products or brands and the usage of products. It also makes the relationship between the sentences in the body text of shampoo advertisement clear and more communicative.